Endoscopic transoral approach to accessory parotid gland. Issue 3 (June 2022) - Lenzi, Riccardo; Matteucci, Jacopo; Muscatello, Luca
Abstract: Objective; Neoplasm of accessory parotid glands are very rare, accounting for only 1% to 7.7% of all parotid gland tumors. External appproaches including parotidectomy or facelift incision are the recommended treatment, allowing a good control over the anterior facial nerve's branches and Stensen's duct, but they require a large flap elevation and leave an external scar. Methods: We report the case of a 76-year-old woman presented with a chief complaint of swelling in the right cheek. The patient underwent ultrasonography, FNAC and MRI which identified a subcutaneous mass over the anterior border of the masseter muscle. Results: An endoscopic-assisted transoral resection was performed, no postoperative complications were recorded. Final histology was consistent with pleomorphic adenoma. Conclusion: In selected cases, the endoscope-assisted transoral approach allow accessory parotid mass excision with better cosmetic results if compared to the transcutaneous approach. Although not negligible, the risk of facial nerve injury is minimized under endoscopic magnification.